Competition between axial anomaly and ferromagnetic ordering in Bi2-xFexSe3–xSx topological insulator: A study of magnetic and magnetotransport properties - Singh R.; Kumar S.; Jain A.; Singh M.; Ghosh L.; Singh A.; Banik S.; Lakhani A.; Patil S.; Schwier E.F.; Shimada K.; Yusuf S.M.; Chatterjee S. (My University, 2025)
The topological insulators Bi2-xFexSe3–xSx have been investigated by the dc-magnetization, magneto-transport and angle resolved photoemission spectroscopy (ARPES) techniques. With doping of Fe and S, a negative giant magneto-resistance (MR) is observed for parallel electric and magnetic fields (H

E). The MR behavior at lower magnetic field can be explained with the semi-classical theory whereas the MR behavior at higher field has been attributed to the axial anomaly. Interestingly, the system reached to the quantum limit at low magnetic field (∼ 4.5T). The magnetic ordering can be explained with the presence of both the RKKY (surface) and van-Vleck (bulk) interaction. The ARPES study reveals that a surface gap is suppressed when the magnetic ordering changes from ferromagnetic to anti-ferromagnetic ordering. The ARPES study and the appearance of quantum oscillations (SdH) in the resistivity pattern reveal that the topological surface property is preserved with the co-doping of Fe and S. © 2022 The Chinese Ceramic Society